Efeitos do teor de umidade da madeira no fresamento de Pinus Elliottii - Pinheiro, Cleverson [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Numerous factors influence the machining of wood, among them we highlight the machining parameters and the properties of this material, having the analysis of roughness as the primary tool for determining these influences. Despite the advancement of knowledge about machining of wood, there is still little information about the influence of these factors and their interactions in the machining process, since some timber industries they run into issues relating to the reduction of rework aimed at correction of roughness of machined wood parts. With this, the objective of analyzing the influence of the moisture content of the wood of Pinus elliottii, their growth rings and the machining direction in the process cutting cylindrical milling tangential, using hard metal tool. Were raised surface quality data measured in terms of roughness parameters Ra and Rt, obtained by the method of mechanical probing move, as well as power consumption and noise emission generated by the cutting process. Planning and analysis of the experiments were based on Taguchi methodology by defining three levels of moisture content (U) in % (8 ≤ U ≤ U 12; 12 < < 16; 16 ≤ U < 20), two levels to the growth rings (initial wood and latewood) and two levels to the cutting direction (up milling and down milling). The data in power consumed and noise emission were analyzed only in terms of the sense of court and the moisture content. The combination of the levels of the factors that brought the best results, in terms of surface quality, noise emission and power consumed has been the machining direction up milling, moisture content between 8 and 12 % and latewood. Statistically significant differences were determined between the levels of the three input factors analyzed by the roughness parameter Rt. Through parameter Ra was determined statistically meaningful only for cutting ... (Complete abstract click eletronic access below)

Inúmeros fatores influenciam a usinagem da madeira, entre eles destacam-se os parâmetros de usinagem e as propriedades deste material, tendo a análise da rugosidade como a principal ferramenta para a determinação destas influências. Apesar do avanço do conhecimento sobre a usinagem da madeira, ainda existe pouca informação sobre a influência destes fatores e suas interações no processo de usinagem, visto que algumas indústrias madeireiras se deparam com questões referentes à redução de retrabalhos que visam à correção da rugosidade das peças de madeiras usinadas. Com isto, objetivou-se analisar a influência do teor de umidade da madeira de Pinus elliottii, de seus anéis de crescimento e dos sentidos de corte, no processo de fresamento cilíndrico tangencial, utilizando ferramenta de metal duro. Foram levantados dados de qualidade superficial medidos em termos dos parâmetros de rugosidade Ra e Rt, obtidos pelo método de apalpamento mecânico, bem como dados de potência consumida e emissão sonora gerados pelo processo de usinagem. O planejamento e análise dos experimentos se basearam na metodologia de Taguchi, definindo três níveis de teor de umidade (U) em % (8 ≤ U <12; 12 ≤ U <16; 16 ≤ U < 20), dois níveis para os anéis de crescimento (lenho inicial e lenho tardio) e dois níveis para o sentido de corte (concordante e discordante). Os dados de potência cosumida e emissão sonora foram analisados somente em termos do sentido de corte e do teor de umidade. A combinação dos níveis dos fatores que trouxeram os melhores resultados, em termos de qualidade superficial, emissão sonora e potência consumida foi o sentido de corte discordante, teor de umidade entre 8 e 12 % e lenho tardio. Foram determinadas diferenças estatisticamente significativas entre os níveis dos três fatores de entrada analisados pelo ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Umidade; Pinus elliottii; Madeira - Efeito da umidade; Usinagem; Aspereza de superfície; Taguchi, Metodo de (Controle de qualidade); Machining